Isolation of Besnoitia besnoiti from infected cattle in Portugal - Cortes, H.C.E. (2012)
Abstract Besnoitia besnoiti, an obligate intracellular protozoan parasite belonging to the phylum apicomplexa, is the causative agent of bovine besnoitiosis. Besnoitiosis is responsible for significant losses in the cattle industry of Africa and Mediterranean countries due to the high morbidity rate, abortion and infertility in males. The acute stage of disease is associated with the proliferative forms (tachyzoites) and is characterized by fever, whimpery, general weakness and swelling of the superficial lymph nodes. During the following chronic stage, a huge number of cysts are formed mainly in the subcutaneous tissues. This process is non-reversible, and chronic besnoitiosis is characterized by hyper-sclerodermia, hyperkeratosis, alopecia and, in bulls, atrophy, sclerosis and focal necrosis that cause irreversible lesions in the testis. In this paper we report on the identification of large cysts in the skin of a cow and a bull in Portugal, which presented loss of hair and enlargement and pachydermis all over the body. The observation of a two-layered cyst wall within the host cell, the encapsulation of the host cell by a large outer cyst wall, and the subcutaneous localization of the cysts within the host, were characteristic for B. besnoiti. The parasites were isolated from the infected animals and successfully propagated in Vero cells without prior passages in laboratory animals. Morphological characterization of B. besnoiti tachyzoites and the amplification of the 149 bp segment from the internal transcribed spacer 1 (ITS1), aided with specific primers, confirmed the identification of B. besnoiti. Keywords: Besnoitia besnoiti; Bovine besnoitiosis; Portugal; Cyst; In vitro cell culture